2011
DOI: 10.1017/s1368980011002734
|View full text |Cite
|
Sign up to set email alerts
|

Validation of protein and potassium intakes assessed from 24 h recalls against levels estimated from 24 h urine samples in children and adolescents of Turkish descent living in Germany: results from the EVET! Study

Abstract: Objective: Nutrition-related health problems such as obesity are frequent among children and adolescents of Turkish descent living in Germany, yet data on their dietary habits are scarce. One reason might be the lack of validated assessment tools for this target group. We therefore aimed to validate protein and K intakes from one 24 h recall against levels estimated from one 24 h urine sample in children and adolescents of Turkish descent living in Germany. Design: Cross-sectional analyses comprised estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Speed skaters and short-track skaters had mean creatinine levels of approximately 14•5 mmol/d. The middledistance runners, Paralympic cyclist, track cycling sprinters, athletic sprinters and archers had slightly higher mean creatinine levels of approximately 20 mmol/d (range [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In addition, BMX riders had the highest creatinine levels in comparison with others (average approximately 24 mmol/d, with a range of 19-32 mmol/d).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Speed skaters and short-track skaters had mean creatinine levels of approximately 14•5 mmol/d. The middledistance runners, Paralympic cyclist, track cycling sprinters, athletic sprinters and archers had slightly higher mean creatinine levels of approximately 20 mmol/d (range [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In addition, BMX riders had the highest creatinine levels in comparison with others (average approximately 24 mmol/d, with a range of 19-32 mmol/d).…”
Section: Resultsmentioning
confidence: 99%
“…Urinary N as marker for dietary protein as proposed by Isaksson (19) is well accepted as a marker for actual protein intake (13,14,(16)(17)(18) , but assumes N balance. Especially in athletes, this assumption may not always be applicable because athletes potentially have a higher protein turnover than more sedentary subjects (49) .…”
Section: Quality Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, repetitive 24 h dietary recalls for twenty-four homeless individuals in Sheffield found that vitamin B 6 and niacin exceeded the recommended nutrient intake levels (5) , a finding which has also been reported in a study using 48 h dietary recall for ninety-seven homeless men in Paris (10) . The potential for bias similar to that found for the FFQ (30,31) in conjunction with the presence of under-reporting (32,33) and over-reporting (34,35) highlight limitations associated with the sole use of 24 h recall for assessing the nutritional status of the homeless. The potential for bias similar to that found for the FFQ (30,31) in conjunction with the presence of under-reporting (32,33) and over-reporting (34,35) highlight limitations associated with the sole use of 24 h recall for assessing the nutritional status of the homeless.…”
Section: Questionnaire Datamentioning
confidence: 88%
“…Very few studies have reported potassium intake in children obtained from 24-hour urine collections [ 26 , 27 ]. Furthermore, to our knowledge, no Australian study has utilized this methodology.…”
Section: Introductionmentioning
confidence: 99%